Corrigendum on: E‐ and H‐mode transition in a low pressure inductively coupled ammonia plasma. Issue 3 (5th February 2018) - Draškovič‐Bračun, Aljaž; Mozetič, Miran; Zaplotnik, Rok
Abstract : The article by Aljaž Draškovič‐Bračun et al. (ppap.201700105), published online on 18 September 2017, contains a wrong version of Figure2 . This corrigendum is published to correct this.